The Impact of Organizational Learning on Innovation of New Products in Mobilis Corporation - A Case Study of Agencies in Jijel State - معزوزي منيرة; لطرش جمال (Finance and Business Economies Review, 2021)
The study aimed to know the impact that organizational learning has on the innovation of new products in the Mobilis Corporation and the agencies of Jijel state, through its three dimensions: the strategic dimension, the organizational dimension and the cultural dimension. The questionnaire was relied on as a tool for collecting the necessary data on the study variables. The study was conducted by Mobilis agencies. For the Wilayat of Jijel (Jijel, Al-Tahir and Al-Millia). The results of the study concluded that there is a strong positive impact of organizational learning in creating new products due to the effect of the organizational dimension in creating new products, and the absence of an impact on both the strategic and cultural dimensions, The study presented a set of recommendations, the most important of which is the need to take advantage of the dimensions of organizational learning, support innovation in the product, and make continuous improvements in the product and its complementary services.